Value-added Finance Use Animal Waste as Conversion Fertilizer for Vegetable Farming Groups in the West Sinjai Region, Indonesia - Hardianti, H.; Rum, Muh.; Badollahi, Ismail (Manunggal Halim Jaya, 2024)
Agriculture plays a crucial role globally, and addressing the sustainable management of livestock waste is a growing concern. Converting animal waste into fertiliser not only supports organic farming but also offers a sustainable solution for managing livestock waste. This study aims to evaluate the conversion of fertiliser to animal waste and its potential to generate higher economic value for vegetable farmers in the West Sinjai region. By applying theoretical concepts learned in academic settings to real-world problems, this research aims to enhance knowledge regarding the economic benefits of fertiliser conversion. Additionally, it serves as a valuable reference for future studies on the economic impact of using animal waste as a substitute for chemical fertilisers. The primary goal is to determine the financial benefits and added value of using animal waste in place of chemical fertilisers. This research follows a quantitative descriptive approach, using both primary and secondary data. The population consists of secondary crop farmers in the West Sinjai region, and the sample includes six groups of vegetable farmers in Gunung Perak Village. The results indicate that converting fertiliser to animal waste significantly enhances the economic value for farmers in the West Sinjai region, particularly in Gunung Perak Village. This improvement is due to the cost savings from using animal waste compared to chemical fertilisers per production unit, ultimately leading to higher profits for the farmers.